(untitled) (Research, Society and Development, 2021)
This study aimed to investigate the evidence about communication via social media between health professionals and patients who will be submitted to Digestive Endoscopy. It is an integrative review considering the following databases: Pubmed, Web of Science and Scopus. The sample consisted of 08 international articles. As for the location of the study, 04 are Asian, 02 European and 02 North American. The most frequent designs were the prospective randomized study, with 06 studies, followed by the mixed method with 01 and descriptive study with 01. Therefore, 06 studies (75%) presented evidence level 02 (strong) and two (25%), level of evidence 6 (weak). The results point to the scarcity of Brazilian studies that analyze the use of social media as a support tool for health education processes, mainly in the benefits of diagnostic tests as a way of minimizing cancellations and / or ineffective performance.